Comparative chloroplast genome analyses of Paraboea (Gesneriaceae): Insights into adaptive evolution and phylogenetic analysis - Wang, Yifei; Wen, Fang; Hong, Xin; Li, Zhenglong; Mi, Yaolei; Zhao, Bo (Frontiers in Plant Science, 2022)
Paraboea (Gesneriaceae), which is mainly distributed in the karst areas of south China, southwest China and southeast Asia, is an ideal genus to study the phylogeny and adaptive evolution of karst plants. In the study, the complete chloroplast genomes of twelve Paraboea species were sequenced and analyzed. Twelve chloroplast genomes ranged in size from 153166 to 154245 bp. Each chloroplast genome had a typical quartile structure, and relatively conserved type and number of gene components, including 131 genes which are composed of 87 protein coding genes, 36 transfer RNAs and 8 ribosomal RNAs. A total of 600 simple sequence repeats and 389 non-overlapped sequence repeats were obtained from the twelve Paraboea chloroplast genomes. We found ten divergent regions (trnH-GUG-psbA, trnM-CAU, trnC-GCA, atpF-atpH, ycf1, trnK-UUU-rps16, rps15, petL, trnS-GCU-trnR-UCU and psaJ-rpl33) among the 12 Paraboea species to be potential molecular markers. In the phylogenetic tree of 31 Gesneriaceae plants including twelve Paraboea species, all Paraboea species clustered in a clade and confirmed the monophyly of Paraboea. Nine genes with positive selection sites were detected, most of which were related to photosynthesis and protein synthesis, and might played crucial roles in the adaptability of Paraboea to diverse karst environments. These findings are valuable for further study of the phylogeny and karst adaptability of Gesneriaceae plants.